Рыба. История одной миграции: роман / Петр Маркович Алешковский - Алешковский Петр Маркович (Самое время!, 2009)
Экземпляры: РБ (19.01.2012) / Инвентарный номер: 46587 / Цена: 205.60 / Авт.знак: А 49 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6